Investigating Adherence to the 2022 NICE Vitamin D Management Guidelines on MHSOP (Mental Health Services for Older People) Wards - Sooyoung Lee (BJPsych Open)
Aims: Vitamin D deficiency is a widespread problem in older people with reduced ability for production, along with risk factors such as indoor living. Improving adherence to the vitamin D guidelines is a simple and cost-effective method of potentially reducing falls, morbidity and mortality in older patients with risk factors.